Increasing cerebral blood flow improves cognition into late stages in Alzheimer's disease mice. Issue 7 (July 2020) - Bracko, Oliver; Njiru, Brendah N; Swallow, Madisen; Ali, Muhammad; Haft-Javaherian, Mohammad; Schaffer, Chris B
Alzheimer's disease is associated with a 20–30% reduction in cerebral blood flow. In the APP/PS1 mouse model of Alzheimer's disease, inhibiting neutrophil adhesion using an antibody against the neutrophil specific protein Ly6G was recently shown to drive rapid improvements in cerebral blood flow that was accompanied by an improvement in performance on short-term memory tasks. Here, in a longitudinal aging study, we assessed how far into disease development a single injection of anti-Ly6G treatment can acutely improve short-term memory function. We found that APP/PS1 mice as old as 15–16 months had improved performance on the object replacement and Y-maze tests of spatial and working short-term memory, measured at one day after anti-Ly6G treatment. APP/PS1 mice at 17–18 months of age or older did not show acute improvements in cognitive performance, although we did find that capillary stalls were still reduced and cerebral blood flow was still increased by 17% in 21–22-months-old APP/PS1 mice given anti-Ly6G antibody. These data add to the growing body of evidence suggesting that cerebral blood flow reductions are an important contributing factor to the cognitive dysfunction associated with neurodegenerative disease. Thus, interfering with neutrophil adhesion could be a new therapeutic approach for Alzheimer's disease.